LOCAL AND GLOBAL CULTURE IN ENGLISH AS FOREIGN LANGUAGE INSTRUCTION FOR TOURISM STUDENTS: WHAT, WHY AND HOW - IGAP Novita Sari Paragae (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2023)
This article presents the result of a study investigating the local and global culture presented in EFL instruction for tourism students. More specifically, this research investigated the culture inserted by teachers, the reasons for the insertion, and the practice of the insertion of the local and global culture in EFL instruction for tourism students. The study was conducted in the form of qualitative research. The data was collected through interviews and document analysis. The participants of the study were English lecturers teaching English in a tourism study program. The data collected underwent a process of data reduction, data display, and conclusion drawing for the data analysis. Based on the analysis of the study, it was found that (1) local and global cultures were inserted in English instruction although local culture was presented more than global culture, (2) the local culture was inserted to promote cultural identity and nationalism, provide better customer service, enhance cultural awareness, and enhance sustainable tourism; while global culture was inserted to enhance the success of language learning, enhance intercultural communicative competence, and increase employability, and (3) local and global culture were inserted by conducting cultural discussion, cultural comparison and cultural project.